al-Ittija̅h al-Ḥadi̅th fi̅ Ta’li̅mi al-Lughah al-‘Arabiyyah li an-Na̅ṭiqi̅n bi Ghai̅riha̅ wa Taḥdiya̅tiha fi̅ ‘Aṣri al-‘Au̅lamah - Wardhana, Delly; Bahrudin, Uril (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
The orientation of modern Arabic learning has not been implemented optimally in accordance with the desired goals, it has been proven that it has not produced students who can master Arabic. The purpose of this research is to reveal, first: modern orientation in learning Arabic, second: challenges of learning Arabic in the modern era, and third: opportunities for the development of Arabic learning in the modern era. The design of this study uses a qualitative approach with a literature study research type. Research data is collected by reviewing books, journals and other sources relevant to the theme. Data analysis is carried out simultaneously from data collection, sorting, presentation and conclusion. The results of this study are: (1) the modern orientation in learning Arabic is characterized by making Arabic as a means of communication, teaching Arabic language skills as a whole, and learning practices are based on applied linguistic theory (2) it was found that the challenges of learning Arabic in the modern era are the lack of a complete understanding of the orientation of modern Arabic learning, the reality that Arabic language teachers have not mastered applied linguistic theory, and Arabic language learning has not been able to keep up with the development of modern technology, and (3) the opportunity for the development of Arabic language learning in the modern era is the breadth of access to information technology that can be used for learning Arabic. The conclusion of this study is that any challenge in learning Arabic can be turned into an opportunity to develop a more effective learning model.